Chasing dreams: investigating talent identification and development in ballet - Hague, M. M. (Queensland University of Technology, 2017)
The path to becoming a professional dancer is a challenging one, where only the most talented succeed. This research contributes to the field of dance research through its examination of ballet in the Australian context through the unique application of the Foundation, Talent, Elite, Mastery (FTEM) talent identification and development framework originally developed for application within a sporting context (Gulbin, Croser, Morley, & Weissensteimer, 2013). Participants either currently or previously employed as professional ballet dancers, completed surveys and semi-structured interviews that provided data to map each participant`s pathway against the FTEM framework. Findings identified that there are a variety of pathways to achieve success as a dancer, participants valued performance experience and quality of training over quantity, and that neither the age of starting ballet training nor the number of hours of practice undertaken had a statistically significant impact on participants` development of expertise. Training opportunities such as scholarships and summer schools were highly valued by participants, and dance teachers played a key role in identifying talent. While the use of the FTEM framework enabled detailed understanding about the identification and development of talented ballet dancers in Australia, limitations in the utility of the framework were identified. The research offers the first insight, analysis, and evaluation of a framework more commonly used in sport by applying it to the field of dance (i.e., ballet), and proposes a number of suggestions for future research in the field.